Distinct roles of N-terminal fatty acid acylation of the Salinity-sensor protein SOS3 - Villalta, Irene; García, Elena; Hornero-Mendez, Dámaso; Carranco, Raúl; Tello Lacal, Carlos; Mendoza, Imelda; De Luca, Anna; Andrés González, Zaida; Schumacher, Karin; Pardo, José M.; Quintero, Francisco J. (Frontiers in plant science, 2021)
The Salt-Overly-Sensitive (SOS) pathway controls the net uptake of sodium by roots and the xylematic transfer to shoots in vascular plants. SOS3/CBL4 is a core component of the SOS pathway that senses calcium signaling of salinity stress to activate and recruit the protein kinase SOS2/CIPK24 to the plasma membrane to trigger sodium efflux by the Na/H exchanger SOS1/NHX7. However, despite the well-established function of SOS3 at the plasma membrane, SOS3 displays a nucleo-cytoplasmic distribution whose physiological meaning is not understood. Here, we show that the N-terminal part of SOS3 encodes structural information for dual acylation with myristic and palmitic fatty acids, each of which commands a different location and function of SOS3. N-myristoylation at glycine-2 is essential for plasma membrane association and recruiting SOS2 to activate SOS1, whereas S-acylation at cysteine-3 redirects SOS3 toward the nucleus. Moreover, a poly-lysine track in positions 7-11 that is unique to SOS3 among other Arabidopsis CBLs appears to be essential for the correct positioning of the SOS2-SOS3 complex at the plasma membrane for the activation of SOS1. The nuclear-localized SOS3 protein had limited bearing on the salt tolerance of Arabidopsis. These results are evidence of a novel S-acylation dependent nuclear trafficking mechanism that contrasts with alternative subcellular targeting of other CBLs by S-acylation.